PREECLAMPTIC WOMEN WITH FEATURES OF SUBCLINICAL SECONDARY HYPERPARATHYROIDISM HAVE ELEVATED BLOOD PRESSURE LEVELS AFTER DELIVERY. (June 2018) - Colussi, G.; Catena, C.; Fagotto, V.; Pezzutto, F.; Driul, L.; Sechi, L.A.
Abstract : Objective: Calcium supplementation has shown beneficial effects on blood pressure and its metabolism is altered in pregnancy hypertensive-related disorders. In this study, we hypothesized that calcium metabolism can be associated with blood pressure levels in preeclampsia complicated pregnancy. Design and method: A group of 63 multiethnic preeclamptic women (age 35 ± 6 y., 83% European, 14% African, and 3% Hispanic) was consecutively recruited at our Hypertension Unit at 1 month after delivery. We collected clinical and anthropometric variables, blood and urinary samples and performed 24-hours ambulatory blood pressure monitoring (ABPM). We measured plasma and 24-hours urinary calcium, plasma 25-hydroxycholecalciferol, parathyroid hormone (PTH), and creatinine levels, and 24-hours protein excretion. Renal function was estimated by the Modification of Diet in Renal Disease (MDRD) study equation. No women knew to be hypertensive before the current pregnancy or took calcium or vitamin D supplements. Results: At recruitment, 60% of women were taking antihypertensive agents, all of which alpha-methyldopa. For statistical purposes, we divided the group in tertiles according to PTH levels. Women in the third tertile showed biochemical characteristics of secondary hyperparathyroidism with elevated PTH and reduced vitamin D plasma levels (PTH 93 ± 15 pg/ml; 25-hydroxycholecalciferol 20 ± 8 ng/ml). In-office and ABPM blood pressure levels were higher in the third tertile then those in the first. At univariate analysis, PTH was directly associated with in-office systolic (Pearson's correlation coefficient r = 0.417; P < 0.001) and diastolic (r = 0.372; P = 0.003), 24-hours systolic (r = 0.449; P < 0.001) and diastolic (r = 0.401; P = 0.001), daytime systolic (r = 0.421; P < 0.003) and diastolic (r = 0.378; P = 0.002), and nighttime systolic (r = 0.379; P = 0.002) and diastolic (r = 0.442; P < 0.001) blood pressure. Multivariate analysis showed that PTH was associated with systolic and diastolic in-office and 24-hours blood pressure levels independently of age, body mass index, gestational week of delivery, plasma and urinary calcium, vitamin D, renal function, and urinary protein excretion. Conclusions: Plasma PTH is independently associated with blood pressure levels in the post-partum and higher blood pressure was observed in preeclamptic women with subclinical secondary hyperparathyroidism. Further evaluations on the effects of calcium and vitamin D supplementation on blood pressure control of women with a preeclamptic complication should be performed.